2011
DOI: 10.1308/147870811x13137608454858
|View full text |Cite
|
Sign up to set email alerts
|

Treating the torn rotator cuff: current practice in the UK

Abstract: INTRODUCTION The aim of this study was to characterise current rotator cuff repair activity in the UK with emphasis on the management of rotator cuff tears in the elderly population (over 70s). METHODS A one-page web-based survey was created. All British Elbow and Shoulder Society (BESS) members and surgeons who listed the shoulder as an area of specialist interest on the website http://www.specialistInfo.com/ were invited to complete this. RESULTS A total of 103 surgeons completed the survey; most (n=89, 86%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In the transosseous suture cohort, 2/80 shoulders (one operated and one control) and, in the anchor repair group, 14/210 shoulders (seven operated and seven control) were excluded from analysis due to tendon damage during surgery (4), during dissection (5), or mechanical testing (7). Final sample sizes are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the transosseous suture cohort, 2/80 shoulders (one operated and one control) and, in the anchor repair group, 14/210 shoulders (seven operated and seven control) were excluded from analysis due to tendon damage during surgery (4), during dissection (5), or mechanical testing (7). Final sample sizes are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The past decades have seen a major shift in surgical technique not only from open to arthroscopic but also from transosseous to anchor repair [3]. Clinical studies and meta-analyses have found no superiority of one repair technique over the other with regards to functional outcome, pain scores, re-tear rate, or incidence of adhesive capsulitis [4][5][6][7]. But patient-based outcomes of pain, strength, range of motion, stability, or medical imaging indirectly assess tendon strength.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention for stiffness (physiotherapy, arthroscopic release of contractures, and possible injection of hyaluronic acid analogues), roughness (arthroscopic debridement, tuberoplasty and acromioplasty) and other pain generators (subacromio-deltoid bursal injection therapy, synovectomy, acromioclavicular joint resection, LHBT tenoplasty, tenodesis and tenotomy) can all transform a decompensated shoulder into one that compensates very well for the RCT. [72][73][74][75] These interventions are often best performed arthroscopically, and constitute a 'conservative' approach of RCT surgery 76 . Arthroscopic decompression or selective imageguided blockade of the suprascapular nerve and lateral pectoral nerve can be useful adjuncts in gaining pain relief, and the former can be safely repeated using pulsed-radiofrequency treatment (with variable success rates).…”
Section: Treatment Specified By Patho-biomechanicsmentioning
confidence: 99%
“…Despite this, a recent survey of British shoulder surgeons found that over three-quarters of surgeons, presented with a symptomatic cuff tear in a 70 year-old would attempt surgical repair. 24 No specific SHOULDER ORTHOPAEDICS AND TRAUMA 26:1 evidence exists for the outcomes of non-surgical interventions stratified by age.…”
Section: Principles Of Treatmentmentioning
confidence: 99%